Foraminiferal magnesium in Globeriginoides sacculifer - Hastings, D; Russell, Ann D; Emerson, Steven R (Supplement to: Hastings, D et al. (1998): Foraminiferal magnesium in Globeriginoides sacculifer as a paleotemperature proxy. Paleoceanography, 13(2), 161-169, https://doi.org/10.1029/97PA03147, 1998)
Foraminiferal magnesium shows increasing promise as a paleothermometer, but the accuracy and precision are limited by biases introduced by partial dissolution, salinity variations, Mg-rich gametogenic calcite, and contaminant phases. We improved cleaning methods and reduced errors introduced by partial dissolution by sampling from well-preserved cores in the equatorial Atlantic and the Caribbean Sea with different dissolution histories. All cores reveal a synchronous 25% increase in Mg/Ca from the stage 2/3 boundary to the Holocene core top, indicating that dissolution is not a controlling factor. Modern temperatures estimated from core top Mg/Ca are 24.5°-25.0°C, equal to mean annual water temperatures at 50-100 m. We estimate that sea surface temperature increased by 2.6°C (±1.3) from the last glacial maximum to the Holocene. Holocene values were comparable to those during isotope stage 5e. Our data indicate that biases from contaminant phases and partial dissolution can be reduced. This paleothermometer holds promise if uncertainties introduced by salinity variations and gametogenic calcite can be constrained.